Common Fixed Points, Invariant Approximation and Generalized Weak Contractions - Sumit Chandok (International Journal of Mathematics and Mathematical Sciences)
Sufficient conditions for the existence of a common fixed point of generalized -weakly contractive noncommuting mappings are derived. As applications, some results on the set of best approximation for this class of mappings are obtained. The proved results generalize and extend various known results in the literature.